A study of indoor soccer practice by small children (“category fraldinha”): na ecological approach - Itamar Adriano Tagliari; Lenamar Fiorese Vieira (Revista da Educação Física)
The main purpose of this study was to investigate the influence of Futsal practice in the Fraldinha Category (7 and 8 years old) in the Athletic Association of Banco do Brasil (AABB), in Maringa, based on ecological approach. The study is characterized as a descriptive research. The sample, of an intentional kind, was constituted of 10 children. The research was conducted by means of filming, files for observation and a semi-structured interview. Based on the results one can conclude that: the activities that accounted both for significance and temporal persistency were kicking, penalty and collective game. The intepersonal relationships have been basically presented about the children's observations in relation to the coach's explanations, which were not always understood by de children. Besides children had no opportunity to experience different roles during the trainings. There are evidences that the trainings have not given priority to factors that are essential for the development of children at this age.